The Physical Origin of Positive Metallicity Radial Gradients in High-redshift Galaxies: Insights from the FIRE-2 Cosmological Hydrodynamic Simulations - Xunda Sun; Xin Wang; Xiangcheng Ma; Kai Wang; Andrew Wetzel; Claude-André Faucher-Giguère; Philip F. Hopkins; Dušan Kereš; Russell L. Graf; Andrew Marszewski; Jonathan Stern; Guochao Sun; et al. (The Astrophysical Journal)
Using the FIRE-2 cosmological zoom-in simulations, we investigate the temporal evolution of gas-phase metallicity radial gradients of Milky Way–mass progenitors in the redshift range of 0.4 < z < 3. We pay special attention to the occurrence of positive (i.e., inverted) metallicity gradients—where metallicity increases with galactocentric radius. This trend, contrary to the more commonly observed negative radial gradients, has been frequently seen in recent spatially resolved grism observations. The rate of occurrence of positive gradients in FIRE-2 is about ∼7% for 0.4 < z < 3 and ∼13% at higher redshifts (1.5 < z < 3), broadly consistent with observations. Moreover, we investigate the correlations among galaxy metallicity gradient, stellar mass, star formation rate (SFR), and degree of rotational support. Metallicity gradients show a strong correlation with both sSFR and the rotational-to-dispersion velocity ratio ( v _c / σ ), implying that starbursts and kinematic morphology of galaxies play significant roles in shaping these gradients. The FIRE-2 simulations indicate that galaxies with high sSFR ( ${\rm{log}}\,({\rm{sSFR}}\,[{{\rm{yr}}}^{-1}])\gtrsim -9.2$ ) and weak rotational support ( v _c / σ ≲ 1) are more likely—by ∼15%—to develop positive metallicity gradients. This trend is attributed to galaxy-scale gas flows driven by stellar feedback, which effectively redistribute metals within the interstellar medium. Our results support the important role of stellar feedback in governing the chemo-structural evolution and disk formation of Milky Way–mass galaxies at the cosmic noon epoch.